1981
DOI: 10.2105/ajph.71.9.991
|View full text |Cite
|
Sign up to set email alerts
|

The triage experiment in coordinated care for the elderly.

Abstract: Triage is a model project designed to overcome the organizational and financial barriers inhibiting the provision of appropriate care to the elderly. Teams made up of a nurse clinician and a social worker performed assessment, service coordination, and monitoring functions. Services arranged by the teams were financed through a series of waivers on the use of the Medicare Trust Fund. Three hundred and seven Triage clients were followed and compared to a group of 195 elderly in a two-year quasi-experimental The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…During the time of this study, all case management was provided by a single organization. The assessment tool was modified from an original instrument developed as part of Triage, one of the first demonstrations of a Medicare waiver program, 8 and these data have been used in previous studies 9 . The assessment data were entered into a computer system with range checks, checks for internal consistency, and identification of missing data.…”
Section: Methodsmentioning
confidence: 99%
“…During the time of this study, all case management was provided by a single organization. The assessment tool was modified from an original instrument developed as part of Triage, one of the first demonstrations of a Medicare waiver program, 8 and these data have been used in previous studies 9 . The assessment data were entered into a computer system with range checks, checks for internal consistency, and identification of missing data.…”
Section: Methodsmentioning
confidence: 99%
“…During the time of this study, all case management was provided by a single organization. The assessment tool was modified from an original instrument developed as part of Triage, one of the first demonstrations of a Medicare waiver program, 8 and assessment data have been used in earlier studies. Assessment data were entered into a computer system with range checks, checks for internal consistency, and identification of missing data.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluations of these expanded and case managed home services programs also reported similar patient improvement, slightly lower utilization of hospitals and nursing homes, and similar costs associated with patients in the experimental groups. One study made an interesting point when it reported significant cost savings only for the portion of patients who were most at‐risk of institutionalization 7–9 …”
Section: Three Long‐term Care Settingsmentioning
confidence: 99%
“…Comparing patients in nursing homes and the two community settings, it was hypothesized that the patients in the two community settings would: 1) make at least equal progress in their ADL and mobility skills; 2) have comparable postplacement morbidity and hospitalization rates; 3) express greater well‐being; and 4) cost Medicaid less than the 75% cap on per patient expenditures. These hypotheses were based on past reports of equally good care and outcomes for community based and nursing home elders, of greater well‐being of patients participating in family structures versus institutional structures, and of the lower costs associated with New York's 2176 Waiver program 4,5,7–10,15 . Comparing the patients in the two community settings, it was hypothesized that foster home patients would: 1) make more improvement in ADL and mobility skills and 2) cost Medicaid less than would patients receiving NHWW services in their own homes.…”
Section: Three Long‐term Care Settingsmentioning
confidence: 99%